Politik pazarlama iletişimi - Ahmedova, Nazife (My University, 2003)
POLİTİK PAZARLAMA İLETİŞİMİ Son yıllarda bilimin gelişmesiyle, toplumsal ihtiyaçlar da farklılaşmaktadır. Buna bağlı olarak siyasi partiler de ayakta kalabilmek ve hedeflerine ulaşabilmek için, yeni ihtiyaçları karşılamada ve tüketicilere ulaşmada kendini yenileyen pazarlamadan yararlanma yoluna gitmişlerdir. Bu değişimin aracı ise iletişim olmuştur. Bir hizmet pazarlaması da diyebileceğimiz politik pazarlama, iletişim araçlarını kullanarak hitap ettiği kitleye pazarlama sistemi çerçevesinde ulaşmaya çalışmaktadır. Politik Pazarlama İletişimi ise politik propaganda, politik reklam ve halkla ilişkilerle gerçekleşmektedir. Bu çalışmada örnek olarak 3 Kasım Türkiye Genel seçimlerinde partilerin Avrupa Birliği Politikaları, partilerin seçim broşürleri içerik analizine tabi tutularak karşılaştırılmıştır. OVERALL INFORMATION Name and Surname : Nazife Ahmedova Major : Business Administration Program : International Business Administration Thesis Counselor : Assistant to Assos. Prof. Dr. Mehmet Tığlı Typ of Thesis and Date : Master's Degree - August 2003 Political Marketing, Political Marketing Communication

POLİTİCAL MARKETİNG COMMUNICATION Recently, social needs vary with evolving science. Accordingly, political parties had to benefit from an autorenovating marketing in fulfilling new requirements and reaching out consumers in order to survive and achieve their goals. Communication has become the tool of this variation. Political marketing, which may also called as e service marketing, tries to reach the mass that it addresses through communication tools under the framework of marketing system. Whereas, political marketing communication is realized through political propaganda, political advertising and public relations. Here, as an example European Community policies and election brochcures of parties have been subjected to contents analysis and compared during Turkey General Election held on November 3.
Keywords: Siyasi Partiler_Türkiye; Siyasi Propaganda